Hollow fiber porous membrane, hollow fiber porous membrane unit and membrane module
The hollow fiber porous membrane with strategically arranged coarse pores addresses the issue of low bending resistance and flexibility, enhancing water vapor permeability and durability.
Patent Information
- Application Number
- JP2024081479
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-07
- Filing Date
- 2024-05-20
- Publication Date
- 2024-12-19
AI Technical Summary
Conventional hollow fiber membranes suffer from low bending resistance and flexibility, leading to issues such as bending and collapse, which affect water vapor permeability and increase the risk of gas leaks.
The hollow fiber porous membrane is designed with coarse pores that have a major diameter of 10% to 60% of the membrane thickness and are arranged in layers substantially continuously perpendicular to the membrane's thickness direction, enhancing flexibility and handling properties while maintaining water vapor permeability.
The design achieves improved water vapor permeability and flexibility, reducing the risk of bending and gas leaks, resulting in a more durable and efficient membrane module.
Smart Images

Figure 2024177085000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hollow fiber porous membrane, a hollow fiber porous membrane unit, and a membrane module. More specifically, the present invention relates to a hollow fiber porous membrane, a hollow fiber porous membrane unit, and a membrane module that are suitable for use in a humidity control unit used in an air conditioner or a fuel cell system. [Background technology]
[0002] Porous membranes are widely used in medical applications such as blood purifiers for patients with renal failure, and in water treatment applications such as water purifiers. In addition, hollow fiber porous membranes that have pores of a size that allows gas separation exhibit superior gas separation properties among various inorganic membranes, and can be used in environments where chemical resistance and heat resistance are required. There are various gas separation targets using hollow fiber porous membranes, including separation of water vapor and carbon dioxide from the air, and separation of harmful components contained in exhaust gases from factories, etc.
[0003] Hollow fiber porous membranes that are permeable to water vapor are increasingly being used for purposes such as humidifying fuel gas to keep the electrolyte membrane built into fuel cell systems moist, and dehumidifying water in spaces such as offices and homes. Ultrafiltration membranes, microfiltration membranes, and the like are generally widely used as hollow fiber porous membranes, and a method has been proposed in which a polysulfone-based resin, which has excellent strength stability under moist and humidified conditions, is used (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2020-44523 [Patent Document 2] Patent Publication No. 2011-67812 Summary of the Invention [Problem to be solved by the invention]
[0005] However, although the above-mentioned conventional techniques could increase water vapor permeability and suppress gas leakage, there was a problem that the bending resistance of the hollow fiber membrane was low. For example, in the case of a structure in which there are no large voids in the cross section of the hollow fiber membrane and micropores with a diameter of submicron level are scattered in order to improve the strength stability as described in Patent Documents 1 and 2, the hollow fiber membrane has poor flexibility and is difficult to handle when assembling the hollow fiber membrane into a membrane module, so that the hollow fiber membrane may be bent and crushed, which may deteriorate the water vapor permeability and make gas leakage more likely to occur. [Means for solving the problem]
[0006] In order to solve the above problems, the present invention comprises the following configuration.
[0007] A hollow fiber porous membrane having a region in which, in a cross section perpendicular to the longitudinal direction of the hollow fiber porous membrane (hereinafter referred to as the vertical cross section), coarse pores whose major diameter is 10% to 60% of the thickness of the hollow fiber porous membrane and 10 μm or more, are arranged in parallel and approximately continuous layers in a direction perpendicular to the thickness direction of the hollow fiber porous membrane, and the hollow fiber porous membrane has a plurality of such regions in the thickness direction of the hollow fiber porous membrane. Effect of the Invention
[0008] The hollow fiber porous membrane and membrane module obtained by the present invention can be effectively used as a hollow fiber porous membrane and membrane module having excellent water vapor permeability and flexibility. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing a vertical cross section of a hollow fiber porous membrane of the present invention. [Diagram 2] FIG. 2 is a diagram showing the major axis, minor axis, etc. of a coarse pore in a vertical cross section. [Diagram 3] FIG. 13 is a diagram to help explain a method for measuring the distance between regions in which the coarse pores are arranged in parallel and substantially continuously to form layers in a vertical cross section. [Figure 4] FIG. [Diagram 5]FIG. 2 is a block diagram relating to the power supply of a fuel cell vehicle. [Figure 6] FIG. 2 is a schematic diagram showing a method for measuring water vapor permeability. [Figure 7] FIG. 11 is a schematic perspective view illustrating a method for evaluating bending resistance. [Figure 8] FIG. 2 is a schematic diagram showing a method for evaluating durability in an intermittent air test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments.
[0011] The hollow fiber porous membrane of the present invention is a hollow fiber porous membrane having, in a cross section perpendicular to the longitudinal direction of the hollow fiber porous membrane (hereinafter referred to as the vertical cross section), a region in which coarse pores, the major axis of which is 10% to 60% of the thickness of the hollow fiber porous membrane and is 10 μm or more, are arranged in parallel and approximately continuous layers in a direction perpendicular to the thickness direction of the hollow fiber porous membrane, and the hollow fiber porous membrane has a plurality of such regions in the thickness direction of the hollow fiber porous membrane.
[0012] <Hollow fiber porous membrane> Fig. 1 is a cross-sectional view perpendicular to the length direction of a hollow fiber porous membrane according to an embodiment of the present invention. In Fig. 1, in the vertical cross section of the hollow fiber porous membrane 1, there is a region 10 in which a plurality of coarse pores 2 are arranged substantially continuously in parallel to form a layer in a direction Y perpendicular to the thickness direction X of the hollow fiber porous membrane 1, and two regions 10 exist in the thickness direction X of the hollow fiber porous membrane.
[0013] The term "coarse pores" in the vertical cross section of the present invention means voids having a length of 10 μm or more when the long side of the rectangle inscribed in the pore is taken as the major axis. By having a length of 10 μm or more, the hollow fiber porous membrane can be given excellent flexibility. On the other hand, it is preferable that the major axis does not exceed 100 μm. If the major axis exceeds 100 μm, the strength of the hollow fiber porous membrane tends to decrease.
[0014] In the present invention, the region in which the coarse pores are arranged in parallel and substantially continuously to form layers means a region formed when the ends of the inner surface side and the ends of the outer surface side of the coarse pores adjacent to each other in the direction Y perpendicular to the thickness direction X of the hollow fiber porous membrane are connected by a line. When two or more coarse pores are connected in the membrane thickness direction X in one region, the outer surface side end of the coarse pore located on the outermost side of the connected coarse pores and the inner surface side end of the coarse pore located on the innermost side of the connected coarse pores are selected. The existence of multiple layers of such regions in the thickness direction of the hollow fiber porous membrane improves the flexibility of the hollow fiber, improves the handling properties, and suppresses the folding and size change of the hollow fiber. Each region may have some holes that are smaller than the coarse pores, and it is preferable that no coarse pores exist outside the region, but it is acceptable for some coarse pores to be scattered outside the region to the extent that the flexibility of the present invention is not hindered.
[0015] In the hollow fiber porous membrane 1 of the present invention, pores can be formed by inducing phase separation by contacting and diffusing the core liquid into the membrane-forming solution, as described below. Therefore, the formation of coarse pores can be controlled by designing the membrane-forming solution to control the phase separation rate and by controlling the design of the core liquid.
[0016] The major axis of the coarse pores 2 is 10% to 60% of the thickness of the hollow fiber porous membrane. By setting it in this range, the permeation (diffusion) resistance of the coarse pores 2 in the hollow fiber porous membrane 1 is reduced, so that it is possible to increase the water vapor permeability while suppressing leakage when separating the water in the water vapor from the air. In this case, the thickness and major axis of the hollow fiber porous membrane are measured by the method described later.
[0017] Figures 2 and 3 show the major and minor axes of the coarse pores in a vertical cross section.
[0018] The thickness of the hollow fiber porous membrane 1 and the long diameter 3 of the coarse pore 2 can be confirmed by using a scanning electron microscope (SEM) at a magnification that makes it easy to measure the cross section of the hollow fiber porous membrane (for example, a magnification of 1000 times, but depending on the diameter of the hollow fiber porous membrane and the size of the coarse pore, a magnification of 2000 times or 500 times may be used). The long diameter 3 and short diameter 4 of the coarse pore 2 are defined as the long and short sides, respectively, of a circumscribed rectangle 5 of the coarse pore obtained by binarizing an image taken with the SEM using image processing and measurement software (WinROOF, manufactured by Mitani Shoji Co., Ltd.).
[0019] The hollow fiber porous membrane of the present invention preferably has a dense layer on the inner diameter side of the hollow fiber. In a vertical cross section, the dense layer preferably has a thickness of 0.1 μm or more and 0.5 μm or less. Here, the dense layer is a layer having a pore area of 1260 nm2 or less when the vertical cross section is observed with a scanning electron microscope (SEM). 2 This refers to a layer in which no pores exceeding 100% are found. Having a dense layer improves the ability to suppress gas leaks.
[0020] The inner diameter of the hollow fiber porous membrane is preferably 500 μm or more and 1000 μm or less. If the inner diameter is less than 500 μm, when a high flow rate of air is passed through the hollow part of the hollow fiber porous membrane, the pressure from the inlet to the outlet of the hollow part increases, and the hollow fiber porous membrane may break. On the other hand, if the inner diameter exceeds 1000 μm, in a module equipped with the hollow fiber porous membrane, the air flow outside the hollow fiber porous membrane may be biased, and the hollow fiber porous membrane may not be effectively used. In addition, if the hollow fiber porous membrane becomes too thick, the size of the module tends to become large, which is not suitable for space saving.
[0021] The membrane thickness of the hollow fiber porous membrane is preferably 50 μm or more and 300 μm or less. If the membrane thickness is less than 50 μm, the breaking strength of the hollow fiber porous membrane decreases, and the membrane may break when a high flow rate of air is applied. If the membrane thickness is more than 300 μm, the membrane may lack structural control stability during membrane formation, and the membrane formation reproducibility of the voids in the porous membrane may be poor.
[0022] In addition, in order to increase the water vapor permeability of the hollow fiber porous membrane of the present invention, it is preferable that the water permeability is in a somewhat small range rather than being completely nonexistent.
[0023] The hollow fiber porous membrane of the present invention preferably has a porosity of 60% or more and 85% or less throughout the entire hollow fiber porous membrane, and more preferably 70% or more and 85% or less. By having a porosity of 60% or more and 85% or less throughout the entire hollow fiber porous membrane, the density of the polymer skeleton of the main component of the hollow fiber porous membrane is increased, and durability can be improved. If the porosity of the entire hollow fiber porous membrane is less than 60%, the structure of the main component of the hollow fiber porous membrane may increase, and water vapor permeability may decrease. If the porosity exceeds 85%, the polymer aggregation of the main component of the porous membrane may weaken, and durability may decrease.
[0024] The porosity can be determined by the following method. First, hollow fiber porous membranes cut to a certain length are dried for 24 hours in a dryer set at 50°C. Next, the number of hollow fiber porous membranes is adjusted so that the weight after drying is in the range of 1 g to 5 g. The volume of the hollow fiber porous membrane is calculated from the number and length of the hollow fiber porous membranes used, and the outer diameter and inner diameter of the membrane, and the porosity is calculated using the dry weight and the density of the polymer that is the main component of the hollow fiber porous membrane.
[0025] In addition, in the hollow fiber porous membrane of the present invention, the distance between the regions where the coarse pores are arranged in parallel and substantially continuously to form layers is preferably 5% to 20% of the thickness of the hollow fiber porous membrane. If the distance between the regions where the coarse pores are arranged in parallel and substantially continuously to form layers is less than 5% of the thickness of the hollow fiber porous membrane, the polymer aggregation of the main component of the porous membrane may be weakened, and durability may be reduced. If the distance exceeds 20%, the structure where the main component of the hollow fiber porous membrane is aggregated increases, and water vapor permeability may be reduced.
[0026] The distance between the regions in which the coarse pores are substantially continuously arranged in parallel to form layers according to the present invention can be measured by the following method. First, five cross sections are cut out from each of five hollow fiber porous membranes. When extracting hollow fiber porous membranes from a membrane module, any five membranes are extracted. Images of the obtained membrane cross sections are taken using an SEM at a magnification that is easy to measure, and binarized using image processing and measurement software (Mitani Shoji Co., Ltd., WinROOF). From the obtained images, a circumscribing rectangle (I) for the coarse pore (I) in the region on the inner diameter side of the hollow fiber and a circumscribing rectangle (II) for the coarse pore (II) in the region on the outer diameter side of the hollow fiber are obtained. Then, the distance I in the thickness direction X of the hollow fiber porous membrane from the point located on the outer diameter side of the hollow fiber to the surface of the inner diameter of the hollow fiber is measured among the contact points 6 between the circumscribing rectangle (I) and the coarse pore (I). When the coarse pore (I) is observed twice in the thickness direction X of the hollow fiber porous membrane, the measurement is performed for the coarse pore (I) on the outer diameter side. Next, the distance II in the thickness direction X of the hollow fiber porous membrane is measured from the point located on the hollow fiber inner diameter side of the contact point 7 between the circumscribed rectangle (II) and the coarse hole (II) to the hollow fiber outer diameter surface. The distance I and the distance II are measured for each of three arbitrary coarse holes (I) and coarse holes (II). The same calculation is performed for five images taken for each of the five cut cross sections, and the same measurement is performed for five hollow fiber porous membranes. The difference between the sum of the average values of the measurement results of the distance I and the distance II obtained and the thickness of the hollow fiber porous membrane is taken as the average value of the distance between the regions in which the coarse holes are layered in parallel and substantially continuously. In addition, in the hollow fiber porous membrane of the present invention, it is preferable that the average value of the long diameter of the coarse hole (a) relative to the short diameter of the coarse hole (b) is larger than the average value of the long diameter of the coarse hole (b) relative to the short diameter of the coarse hole (a) in the region closest to the hollow fiber inner diameter side in the vertical cross section and the coarse hole (b) in the region closest to the hollow fiber outer diameter side. It is further preferable that the average ratio of the long diameter to the short diameter of the coarse pores (a) is 0.5 or more larger than the average ratio of the long diameter to the short diameter of the coarse pores (b). By making the average ratio of the long diameter / short diameter of the coarse pores (a) larger than the average ratio of the long diameter / short diameter of the coarse pores (b), the hollow fiber porous membrane is less likely to be crushed and the hollow fiber fiber shape is easily maintained.Although the detailed mechanism is unclear, the larger the average value of the long diameter / short diameter of the coarse pores in the region where the coarse pores are arranged in parallel and substantially continuously to form layers, the more the coarse pores in the region tend to be densely packed. Therefore, it is presumed that the strength of the hollow fiber porous membrane is improved by dispersing the coarse pores on the outer diameter side of the hollow fiber porous membrane compared to the coarse pores on the inner diameter. The average value of the long diameter / short diameter of the coarse pores (a) is preferably 2.0 or more and 8.0 or less. The average value of the long diameter / short diameter of the coarse pores (b) is preferably 1.0 or more and less than 3.0. When the average value of the long diameter / short diameter of the coarse pores (b) is less than 1.0, it becomes difficult to control the size of the coarse pores (b), and the size variation of the coarse pores (b) becomes large, and the hollow fiber porous membrane is likely to have a partially weak spot. When the average value is 3.0 or more, the pressure resistance of the hollow fiber porous membrane may be reduced. The long diameter and short diameter of the coarse pores (a) and (b) can be measured by the following method. First, five cross sections are cut out from each of the five hollow fiber porous membranes. When extracting hollow fiber porous membranes from a membrane module, five of them are taken out. Images of the obtained membrane cross sections are taken using an SEM at a magnification that is easy to measure, and for the coarse pores that are almost continuously arranged in parallel, the major axis and minor axis of three arbitrary coarse pores (a) in the region located closest to the hollow fiber inner diameter side in the hollow fiber porous membrane cross section and the arbitrary coarse pores (b) in the region located closest to the hollow fiber outer diameter side are measured, and the major axis and minor axis of each are calculated. For five images taken for each of the five cut cross sections, the major axis and minor axis of each coarse pore are calculated in the same manner, and the same measurement is performed for five hollow fiber porous membranes. The average value of all the major axis and minor axis values obtained on the hollow fiber outer diameter side is taken as the average value of the major axis and minor axis of the coarse pores (b). The average value of all the major axis and minor axis values obtained on the hollow fiber inner diameter side is taken as the average value of the major axis and minor axis of the coarse pores (a).
[0027] In addition, the ratio of the long diameter to the thickness of the hollow fiber porous membrane was calculated from the average value of the measured total length diameter (6 locations x 5 cross sections x 5 pieces per cross section of one hollow fiber porous membrane) and the membrane thickness obtained above.
[0028] In addition, the hollow fiber porous membrane of the present invention preferably has a region in which many pores smaller than the coarse pores exist between the outer surface of the hollow fiber and the coarse pore (b) in the vertical cross section. By having this region (hereinafter, strength retention layer), the strength of the hollow fiber porous membrane can be improved. The thickness of the strength retention layer is preferably 5% to 20% of the thickness of the hollow fiber porous membrane. The thickness of the strength retention layer can be measured by the following method. First, five hollow fiber porous membranes are cut out at five locations to obtain cross sections. When extracting hollow fiber porous membranes from a membrane module, any five membranes are extracted. The obtained membrane cross sections are observed by taking images using a SEM at a magnification that is easy to measure, and binarized using image processing and measurement software (Mitani Shoji Co., Ltd., WinROOF). From the obtained images, circumscribed rectangles for the coarse pores in the region on the outer diameter side of the hollow fibers are obtained. Then, the thickness of the hollow fiber porous membrane in the thickness direction X is measured from the point on the hollow fiber outer diameter side of the contact point between the circumscribed rectangle and the coarse hole to the outer diameter surface of the hollow fiber. The distance is measured for each of three arbitrary coarse holes. The same calculation is performed for five images taken of each of the five cut cross sections, and the same measurement is performed for five hollow fiber porous membranes. The average of the obtained thickness measurements is taken as the thickness of the strength retention layer.
[0029] In addition, in the vertical cross section of the hollow fiber porous membrane of the present invention, the total area of the coarse pores (a) and (b) is preferably 25% or more and 40% or less of the area of the vertical cross section. If the total area ratio of the coarse pores (a) and (b) is less than 25%, the structural portion in which the main component of the hollow fiber porous membrane is aggregated increases, and water vapor permeability may decrease. If it exceeds 40%, the polymer aggregation of the main component of the porous membrane may weaken, and durability may decrease. As a method for calculating the ratio of the total area of the coarse pores (a) and (b) in the vertical cross section, for example, the image obtained using a scanning electron microscope (SEM) at a magnification that makes it easy to measure the cross section of the hollow fiber porous membrane (for example, a magnification of 1000 times, but depending on the diameter of the hollow fiber porous membrane, a magnification of 2000 times or 500 times may be used), is binarized using image processing and measurement software (Mitani Shoji Co., Ltd., WinROOF), and the ratio can be calculated from the area of the coarse pores (a) and (b) obtained and the vertical cross section. The material constituting the hollow fiber porous membrane of the present invention is not particularly limited, and examples thereof include polysulfone-based polymers, polystyrene, polyurethane, polyethylene, polypropylene, polycarbonate, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl chloride, and polyester. Among these, from the viewpoint of excellent heat resistance and easy formation of the hollow fiber porous membrane, it is preferable that the hollow fiber porous membrane contains a polysulfone-based polymer. Although there is no particular limitation on the content of the polysulfone-based polymer, it is preferable that the polysulfone-based polymer is the main component of the porous membrane. The main component means that the raw material is contained in an amount of 90% by mass or more and 100% by mass or less with respect to 100% by mass of the entire hollow fiber porous membrane.
[0030] Here, the polysulfone-based polymer is a polymer having an aromatic ring, a sulfonyl group, and an ether group in the main chain, and examples thereof include polysulfone, polyphenylsulfone, polyethersulfone, polyarylethersulfone, etc., and for example, polysulfone-based polymers represented by the following chemical formulas (1) and / or (2) are preferably used. In the formula, n is an integer of 1 or more, and preferably 50 to 80. When n has a distribution, the average value is taken as n.
[0031] The polysulfone-based polymer may be copolymerized with other monomers or may be modified within a range that does not impair the effects of the present invention. When copolymerized with other monomers, the copolymerization ratio of the other monomers is preferably 10% by mass or less based on the entire polysulfone-based polymer.
[0032] [ka]
[0033] Specific examples of polysulfone-based polymers include polysulfone-based polymers such as "Udel Polysulfone" P-1700, P-3500 (manufactured by Solvay), "Ultrason" S3010, P3010, S6010 (manufactured by BASF), "Victrex" (manufactured by Sumitomo Chemical Co., Ltd.), "Radel" polyphenylsulfone R-5000NT (manufactured by Solvay), "Veradel" polyethersulfone 3000MP (manufactured by Solvay), and "Ultrason" E (manufactured by BASF).
[0034] When the material constituting the hollow fiber porous membrane of the present invention is mainly composed of a polysulfone-based polymer, it is preferable that the material contains a hydrophilic polymer. Examples of hydrophilic polymers include polyalkylene oxide, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, etc., and among these, hydrophilic polymers having a glass transition point higher than 150°C are preferably used because they can provide a hollow fiber porous membrane with excellent heat resistance. Polyvinylpyrrolidone has excellent compatibility with polysulfone-based polymers and a high glass transition point of 180°C, so it is preferable for use in humidifying fuel cell systems. In other words, it is particularly preferable that the hollow fiber porous membrane of the present invention contains a polysulfone-based polymer and polyvinylpyrrolidone. The content of polyvinylpyrrolidone in 100% by mass of the hollow fiber porous membrane is preferably 0.01% by mass or more and 5% by mass or less, and more preferably 4% by mass or less. When the content of polyvinylpyrrolidone in the hollow fiber porous membrane is 5% by mass or more, the hydrophilicity or swelling property of polyvinylpyrrolidone decreases as the environment in which the fuel cell is used becomes high temperature and / or low humidity, so that it may be difficult to maintain the performance of water vapor permeability. In addition, the content of polyvinylpyrrolidone in 100% by mass of the hollow fiber porous membrane is preferably 1% by mass or more, and more preferably 2% by mass or more. When the content of polyvinylpyrrolidone in the hollow fiber porous membrane is less than 1% by mass, the hydrophilicity of the hollow fiber porous membrane decreases, so that the membrane may not absorb water vapor easily when it comes into contact with water vapor. When the polymer composition of the hollow fiber porous membrane is known, the polyvinylpyrrolidone content in the hollow fiber porous membrane can be measured using an NC analyzer after weighing the hollow fiber porous membrane dried in a dryer (details are described in the evaluation method [5] in the Examples). In addition, when the polymer composition is unknown, the hollow fiber porous membrane can be dissolved in deuterated dimethyl sulfoxide and the sample can be measured using a Fourier transform nuclear magnetic resonance device.
[0035] <Method of manufacturing hollow fiber porous membrane> As an embodiment of the method for producing the hollow fiber porous membrane of the present invention, the following method for producing the hollow fiber porous membrane can be mentioned. That is, when a membrane-forming stock solution (polysulfone-based polymer concentration is preferably 20% by mass to 35% by mass, more preferably 25% by mass to 30% by mass, as described later) in which a polysulfone-based polymer and polyvinylpyrrolidone are dissolved in a mixed solution of a good solvent for polysulfone (preferably N,N-dimethylacetamide, dimethylsulfoxide, dimethylformamide, N-methylpyrrolidone, dioxane, etc.) and a poor solvent is discharged from a double ring die, a core liquid is flowed inside, and after running 350 mm in a dry section, it is coagulated in a coagulation solution. At this time, since the humidity of the dry section has an effect, by adjusting the phase separation behavior near the outer surface by supplying water from the outer surface of the membrane during running in the dry section, it becomes possible to enlarge the pore size and form multiple layers in which coarse pores are layered in parallel in a substantially continuous manner. As a result, it is also possible to reduce the permeation resistance during humidification. However, if the relative humidity is too high, the solidification of the stock solution on the outer surface becomes dominant, and the pore size becomes small without forming large pores, which tends to increase the permeation resistance during humidification. Therefore, a relative humidity of 60 to 90% is preferable. In addition, it is preferable to use a core liquid composition based on the solvent used in the membrane-forming stock solution from the viewpoint of process suitability. As an example of the core liquid concentration, when N,N-dimethylacetamide is used, an aqueous solution with a concentration of 10 to 60 mass%, or even 20 to 50 mass%, is preferably used.
[0036] The solidified hollow fiber porous membrane is washed with warm water at 40°C to 90°C and wound up. If the washing temperature is less than 40°C, the organic solvents and the like are not washed off sufficiently, and the eluted material from the hollow fiber porous membrane may affect its use. If the washing temperature is more than 90°C, the hydrophilic polymer is washed off more than necessary, and the hydrophilicity of the hollow fiber porous membrane may decrease.
[0037] Next, a heat treatment is performed to fix the pore size to the desired size, and a dry hollow fiber porous membrane is obtained. The heat treatment is a process in which the wet porous membrane is dried to reduce the size of the pores. After this treatment, it is no longer necessary to keep the hollow fiber porous membrane moist (by adding glycerin or filling it with water).
[0038] As a method for heat treating the hollow fiber porous membrane, it is preferable to divide the hollow fiber porous membrane into several hundreds to several thousands of pieces and dry them for 30 minutes or more in a dry heat dryer at 40° C. to 170° C., more preferably 50° C. to 170° C., and even more preferably 50° C. to 150° C.
[0039] If the drying temperature is lower than 40°C, it takes a long time to dry, and depending on the external atmosphere, it may be difficult to control the temperature and the size of the pores may not be controlled. If the drying temperature is higher than 170°C, when a polysulfone-based polymer is used, the glass transition point of the polymer approaches, which may damage the hollow fiber porous membrane. The drying time is preferably 30 minutes or more. More preferably, it is 5 hours or more. There is no particular upper limit to the drying time, but it is preferably within 72 hours in consideration of work efficiency. If the drying time is shorter than 30 minutes, the moisture in the hollow fiber porous membrane cannot be completely removed, and there may be some areas that have not been heat-treated. In this case, the pores of the hollow fiber porous membrane may be both shrunk and unshrunk, which may result in insufficient separation of the moisture and air in the water vapor, leading to air leakage. In addition, when heat is applied during use, the size of the pores in the areas where the pores are not shrunk may change, causing the initial performance to fluctuate. One method for achieving a porosity of 60% or more and 85% or less throughout the entire hollow fiber porous membrane is to control the concentration of polysulfone-based polymer in the membrane-forming solution in order to adjust the skeletal density of the polymer that is the main component of the hollow fiber porous membrane.
[0040] The polysulfone-based polymer concentration in the membrane-forming solution is preferably 20% by mass or more and 35% by mass or less, more preferably 25% by mass or more and 30% by mass or less, based on the total mass of the membrane-forming solution. If the polysulfone-based polymer concentration in the membrane-forming solution is less than 20% by mass, the porosity of the hollow fiber porous membrane increases, and the durability tends to decrease.
[0041] The viscosity of the membrane-forming solution is preferably 30 Poise or more and 100 Poise or less, more preferably 40 Poise or more and 80 Poise or less. If the viscosity of the membrane-forming solution is higher than 100 Poise, the layer without coarse pores on the inner diameter side of the hollow fiber porous membrane becomes thick, or it becomes difficult to obtain coarse pores, and the water vapor permeability tends to be low. If the viscosity is less than 30 Poise, the layer without coarse pores on the inner diameter side of the hollow fiber porous membrane tends to become thin, and the coarse pores on the outer diameter side tend to reach the membrane surface and form membrane surface holes, so the strength of the hollow fiber porous membrane tends to be low and the membrane tends to be weak.
[0042] In order to obtain a hollow fiber porous membrane having a plurality of regions in which the coarse pores are arranged in parallel and substantially continuously in layers in the thickness direction of the membrane in a vertical cross section, it is preferable to use a solution having a high diffusivity in the membrane-forming solution as the core liquid. If a solution having a low diffusivity is used as the core liquid, precise control of the pores becomes difficult, and membrane formation may become impossible.
[0043] Furthermore, it is also preferable to control the viscosity of the membrane-forming solution, the condensability of the membrane-forming solution and the core liquid, etc. For example, if the viscosity of the membrane-forming solution is high, the diffusion speed of the core liquid is slower than that of the membrane-forming solution, and the growth of the coarse pores in the process of forming the coarse pores in the hollow fiber porous membrane is slower and the length of the coarse pores is shorter. Similar growth of coarse pores is also considered when the core liquid has viscosity.
[0044] Furthermore, if a highly cohesive liquid such as water is used as the core liquid, only the surface in contact with the core liquid will coagulate, and large coarse pores may be formed near the surface of the membrane that is not in contact with the core liquid.
[0045] In other words, in order to control the size of the coarse pores, it is important to design the membrane-forming solution and the core liquid to control the phase separation rate.
[0046] Even if the same polymer is used, the viscosity of the film-forming solution will be high if the polymer has a high molecular weight, and low if the polymer has a low molecular weight. Furthermore, the viscosity will change depending on the amount added. It is preferable to select the type of polymer, the molecular weight of the polymer, and the amount of the polymer added so that the viscosity of the film-forming solution is in the range of 30 Poise to 100 Poise.
[0047] Regarding the ratio of the solvent in the core liquid, increasing the ratio of an organic solvent that dissolves the polymer in the membrane-forming solution (good solvent: aprotic polar solvents such as dimethylformamide, N-dimethylacetamide, N-methyl-2-pyrrolidone, etc.) slows down the aggregation that occurs during membrane formation of the polymer, making it difficult to form coarse pores. If the ratio of a solvent that is insoluble in the polymer in the membrane-forming solution (poor solvent) is high, rapid aggregation occurs between the core liquid and the membrane-forming solution, making it easier to form coarse pores. In other words, the formation of coarse pores can be controlled by adjusting the type and ratio of the solvent in the core liquid. The concentration of the good solvent in the core liquid is preferably 10% by mass or more and 60% by mass or less, more preferably 20% by mass or more and 50% by mass or less.
[0048] The size of the coarse pores can also be controlled by combining a low-viscosity core liquid such as water, a low-viscosity solvent, or a water / low-viscosity solvent solution with a high-viscosity core liquid such as glycerin or a solvent containing a polymer such as PVP with the membrane-forming solution.
[0049] The polyvinylpyrrolidone added to the membrane forming solution as the hydrophilic polymer has a weight average molecular weight of about 10,000 to 1,200,000, preferably about 40,000 to 1,200,000, and is preferably used at a ratio of 5 to 50 mass% and more preferably 8 to 30 mass% per 100 mass% of the polysulfone-based polymer. If it is less than 5 mass% relative to the polysulfone-based polymer, it is not possible to impart hydrophilicity to the surface of the hollow fiber porous membrane, and there is a concern that the affinity with water vapor may be reduced. If it exceeds 50 mass%, the strength of the hollow fiber porous membrane may be reduced, making it difficult to form the membrane.
[0050] <Hollow fiber porous membrane unit> The hollow fiber porous membrane unit of the present invention is a hollow fiber porous membrane of the present invention covered with a covering yarn, and two or more hollow fiber porous membranes are arranged side by side and wrapped around the whole with a thread-like or belt-like material to maintain this state. The wrapping method may be wrapping with multiple threads or belts, or wrapping in a spiral shape with a single thread or belt. The point is that it is sufficient to be able to maintain the state in which the rod-like or thread-like materials are arranged side by side.
[0051] As the covering yarn, it is preferable to use one or more of bulky and stretchable crimped yarn, textured yarn, or spun yarn. If these yarns are used as the covering yarn, the hollow fiber porous membrane unit can be completed online without damaging the hollow fiber porous membrane when the covering yarn is wound spirally around the hollow fiber porous membrane. Specifically, a fiber with a stretch rate of more than 1% is preferable. Here, "online" refers to completing the membrane unit within a series of processes up to winding up the hollow fiber porous membrane discharged from the nozzle.
[0052] The material of the covering yarn is not particularly limited, but examples include polyester, polypropylene, polyphenylene sulfide, and the like.
[0053] <Membrane module> The membrane module of the present invention is a membrane module including the hollow fiber porous membrane of the present invention or the hollow fiber porous membrane unit of the present invention. More specifically, the hollow fiber porous membrane or hollow fiber porous membrane unit of the present invention is filled in a cylindrical or rectangular case, and both ends of the hollow fiber porous membrane or hollow fiber porous membrane unit are fixed with a potting material. As the potting material, polyurethane, epoxy, silicone, nylon, etc. are appropriately selected and used. An example of a method for producing the membrane module of the present invention is as follows. First, the hollow fiber porous membrane is cut to a required length, and the required number is bundled and placed in a cylindrical case. Then, both ends are temporarily capped, and the potting material is placed on both ends of the hollow fiber porous membrane. At this time, the method of putting the potting material while rotating the module with a centrifuge is a preferred method because the potting material is filled uniformly. After the potting material has solidified, both ends of the hollow fiber porous membrane are cut so that both ends are open, and a membrane module can be obtained.
[0054] <Possible applications of membrane modules> The membrane module of the present invention is applicable to air conditioners such as dehumidifiers, humidifiers, and dehumidifiers, fuel cell systems, and desiccant air conditioning systems.
[0055] <Air conditioner> Next, an air conditioner including a membrane module including a hollow fiber porous membrane according to an embodiment of the present invention will be described. The air conditioner is a device for controlling humidity in general homes, buildings, offices, factories, etc., such as a humidifier, dehumidifier, dehumidifier and air conditioner.
[0056] The air conditioner of the present invention is a device in which the humidity of the taken-in outdoor air is adjusted by the above-mentioned membrane module. An example of a schematic diagram of an air conditioner is shown in Figure 4. When outdoor air is taken into the air conditioner 20, it passes through an air filter 21, a cooling coil 22, a heating coil 23, a membrane module 24, and a blower 25 in that order, and is then supplied to the room. The cooling coil 22 and the heating coil 23 operate depending on whether the room is to be humidified or dehumidified. Humidification or dehumidification may also be performed by adding a desiccant to the hollow fiber porous membrane of the membrane module 24.
[0057] <Fuel cell system> Next, a fuel cell system including a membrane module including a hollow fiber porous membrane according to an embodiment of the present invention will be described. This fuel cell system is applicable to, for example, fuel cell vehicles and household fuel cells.
[0058] A fuel cell system includes at least the above-mentioned membrane module 31 and a fuel cell 32. An example of this fuel cell system is, without particular limitation, a system in which air humidified using a membrane module and / or hydrogen are supplied to a fuel cell while supplying power. In the case of a fuel cell vehicle, for example, as shown in FIG. 5, the obtained power is supplied to a motor 34 and a battery 35 via a power control unit 33. In addition, the above-mentioned membrane module 31 is built into a metal or resin housing in order to function as a humidifier, and the required specifications can be adjusted by freely changing the number of membrane modules installed depending on the application. EXAMPLES
[0059] The present invention will be described in more detail below based on examples. Note that the present invention is not limited to the following examples. The evaluation methods in the examples are described in the following [1] to [7]. [1] Measurement of hollow fiber porous membrane dimensions The hollow fiber porous membrane was cut in the membrane thickness direction with a single blade and set in a microwatcher (Keyence Corporation, VH-Z100). If the cross section of the hollow fiber porous membrane was crushed by cutting, the membrane was cut again until it became approximately a perfect circle. The cross section of the hollow fiber porous membrane was observed with a 1000x lens, the membrane thickness width of the hollow fiber porous membrane was specified on the monitor screen on which the cross section was projected, and the numerical value displayed on the monitor screen was read. The inner diameter of the hollow fiber porous membrane was also displayed on the monitor screen by specifying the width of the hollow part. Five arbitrary hollow fiber porous membranes present in the membrane module were extracted, and the same measurement was performed, and the average value was calculated to be the inner diameter and membrane thickness of the hollow fiber porous membrane. [2] Preparation of samples for SEM observation of hollow fiber porous membrane cross section The hollow fiber porous membrane obtained by the membrane production was soaked in water for 1 hour to make it wet, then frozen in liquid nitrogen and quickly folded to prepare a sample for observing the cross section of the hollow fiber porous membrane. If the hollow part of the hollow fiber porous membrane or the voids in the membrane thickness part were blocked, the sample was prepared again. Blockage of the hollow part may occur when the hollow fiber porous membrane is deformed in the direction of stress during the cutting process.
[0060] When using SEM images in each of the following methods, the samples for observation were prepared using the method described herein and the images were obtained. [3] Measurement of macropores and the distance between regions where the macropores are arranged in parallel and almost continuously to form layers A 1,000x magnification image of the cross section of one hollow fiber porous membrane was taken with an SEM and imported into a computer. Next, the number of pixels of the scale bar showing a known length in the SEM image was measured on an image processing software, and the length per pixel (μm) was calculated. The size of the imported image was 126.98 μm horizontal x 95.24 μm vertical. The contrast and brightness were adjusted to make the pores in the mesh structure easier to recognize, making the pores black and the membrane white, and then a threshold was set to obtain a binarized image for analysis.
[0061] For the coarse holes arranged in parallel in a substantially continuous manner in the image, the long and short diameters of three arbitrary coarse holes located on the outer surface side and the inner surface side of the hollow fiber porous membrane were measured. In addition, the distance I between the coarse hole located on the inner surface side of the hollow fiber porous membrane and the outer surface of the hollow fiber porous membrane, the distance II between the coarse hole located on the outer surface side of the hollow fiber porous membrane and the inner surface of the hollow fiber porous membrane, and the thickness of the strength retaining layer were also measured in the same manner. The same measurement was performed on five captured images of one hollow fiber porous membrane. Four arbitrary hollow fiber porous membranes present in the membrane module were further extracted and the same measurement was performed, and the average value of the ratio of the long diameter to the short diameter was calculated, which was taken as the ratio of the long diameter to the short diameter.
[0062] In addition, the ratio of the major axis to the thickness of the hollow fiber porous membrane was calculated from the average measured overall axis diameter and the membrane thickness obtained above.
[0063] The difference between the sum of the average values of the measured distances I and II and the film thickness obtained above was taken as the distance between the regions in which the coarse pores were arranged in parallel and substantially continuously to form layers.
[0064] The average value of the measured thicknesses of the strength retaining layer was calculated and regarded as the thickness of the strength retaining layer.
[0065] [4] Measurement of the total area of macropores A 1,000x magnification image of the cross section of one hollow fiber porous membrane was taken using an SEM and imported into a computer. Next, the number of pixels on the scale bar showing a known length in the SEM image was measured using image processing software, and the length per pixel (μm) was calculated. The size of the imported image was 126.98 μm horizontal x 95.24 μm vertical. The contrast and brightness were adjusted to make the pores in the meshwork structure easier to identify, with the pores appearing black and the membrane appearing white, after which a threshold was set and a binarized image was obtained. To extract the locations of coarse pores from the obtained image, a pixel area of 10 μm was selected. 2 Pores with less than 100% area were removed and the total area of the remaining coarse pores was analyzed.
[0066] Next, the contrast and brightness of the same SEM image were adjusted, the entire cross section of the hollow fiber porous membrane was whitened, and then the cross section was inverted to blacken it, and the area of the blackened parts was analyzed. Four additional hollow fiber porous membranes were randomly selected from the membrane module, and the same measurements were performed to calculate the average total area of the coarse pores and the average cross-sectional area of the hollow fiber porous membrane. The ratio of the average total area of the coarse pores to the average cross-sectional area of the hollow fiber porous membrane obtained was taken as the ratio of the total area of the coarse pores in the cross section of the hollow fiber porous membrane.
[0067] [5] Measurement of porosity of hollow fiber porous membrane One hundred hollow fiber porous membranes with a length of 30 cm were cut out and dried in a 50°C dryer for 24 hours to obtain the dry weight (dw, unit: g). The volume of the hollow fiber porous membrane (V, unit: cm) was calculated from the outer diameter, inner diameter, number, and length of the hollow fiber porous membrane. 3 The density of the polymer that is the main component of the hollow fiber porous membrane (ρ, unit: g / cm 3) was used to calculate the porosity using the following formula: The density of the polymer that is the main component of the hollow fiber porous membrane can be measured with a density meter, and the obtained value can be used.
[0068] Porosity (%) of the entire hollow fiber porous membrane = [1-(dw / (V×ρ))]×100 [6] Measurement of polyvinylpyrrolidone (PVP) content in hollow fiber porous membrane The hollow fiber porous membrane was dried in a dryer at 120°C for 5 hours and cut into a length of about 5 mm. After weighing, the nitrogen content of the hollow fiber porous membrane in the dry state was measured using an NC analyzer. When the main component of the hollow fiber porous membrane is polysulfone and PVP is included as a hydrophilic polymer, the membrane does not contain any nitrogen-derived substances other than PVP, so the PVP content (X) of the porous membrane in the dry state was calculated from the nitrogen content (N). The PVP content (Y) of the polysulfone standard can also be calculated from the obtained PVP content (X). X: PVP content (%, based on the dry porous membrane) = (N x 111 / 14) x 100 Y: PVP content (%, based on polysulfone) = [X / (100-X)] x 100. [7] Measurement of water vapor transmission rate The water vapor permeability was measured as follows.
[0069] First, the membrane module was connected as shown in Figure 6. Using the membrane module, dry air at a temperature of 100°C and a pressure of 170 kPaG was passed inside the hollow fiber porous membrane, and humidified air at a temperature of 100°C, a dew point temperature of 90°C, and a pressure of 160 kPaG was passed from the outside of the hollow fiber porous membrane in a single-pass cross flow, and the water vapor permeation rate per unit time was measured. 2 The water vapor recovery rate was calculated from the ratio of the water vapor flow rate (g / hr) of the humidified air supplied to the outside of the hollow fiber porous membrane to the water vapor flow rate (g / hr) of the air coming out from the inside of the porous membrane, and was evaluated according to the following criteria. A (good): Water vapor transmission rate (g / cm 2 / hr / kPa) is 0.025 or more. B (Acceptable): Water vapor transmission rate (g / cm 2 / hr / kPa) is greater than or equal to 0.015 and less than 0.025. C (unacceptable): Water vapor transmission rate (g / cm 2 / hr / kPa) is less than 0.015. [8] Bend resistance evaluation The following description will be given with reference to Fig. 7. A hollow fiber porous membrane 51 was placed along a cylinder 50 having a diameter of 300 mm with the cylinder at an embrace angle of 0° (see Fig. 7(a)), and the hollow fiber porous membrane was bent around the cylinder by rotating it five times. The hollow fiber porous membrane 51 was observed with an optical microscope before and after the bending operation, and the bending resistance was evaluated according to the following criteria. A (good): The hollow fiber porous membrane shows no signs of bending or crushing even after 500 repeated bending operations. B (Acceptable): The hollow fiber porous membrane shows no signs of folding or crushing even after 100 repeated bending operations. C (unacceptable): The bending operation was repeated less than 100 times, and some of the hollow fiber porous membrane was broken or crushed. [9] Durability evaluation using intermittent air testing Durability evaluation by air intermittent test was measured as follows. First, the membrane module was connected as shown in Figure 8. Water vapor was flowed on the outside of the hollow fiber porous membrane of the membrane module, and the temperature of the membrane module body was maintained at 95°C or higher. One side of the inside of the hollow fiber porous membrane of the membrane module was sealed with a pressure sensor, and air was applied intermittently from the other side (ON: 200 kPa for 10 seconds, OFF: 0 kPa for 5 seconds, one cycle for 15 seconds). At this time, when the pressure sensor in the ON state became less than 150 kPa, it was determined that damage had occurred to the membrane, and the test was stopped. Durability was evaluated according to the following criteria based on the number of cycles from the start of the test to the end of the test. A (Good): The pressure sensor did not drop below 150 kPa even after 100,000 cycles. B (Acceptable): The pressure sensor did not drop below 150 kPa even after 10,000 cycles. C (Unacceptable): The pressure sensor reached 150 kPa or more after fewer than 10,000 cycles.
[0070] Example 1 A total of 100% by mass of 28% polysulfone (Solvay's "Udel" P-3500), 3.0% by mass of polyvinylpyrrolidone (BASF's K30), 68% by mass of N,N-dimethylacetamide, and 1% by mass of water were heated and dissolved to prepare a membrane-forming stock solution. A total of 100% by mass of a solution of 30% by mass of N,N-dimethylacetamide and 70% by mass of water was used as the core liquid.
[0071] The membrane forming solution was sent to the spinneret section and discharged from the outer tube of the orifice-type double-tube nozzle, and the core solution was discharged from the inner tube. The discharged membrane forming solution passed through a humidity-controlled dry zone atmosphere, and then led to a coagulation bath and passed through a water washing process at 40°C, and the resulting wet hollow fiber porous membrane was wound up into a bundle. The hollow fiber porous membrane had an inner diameter of 718 μm and a membrane thickness of 104 μm. The wound bundle of hollow fiber porous membranes was dried in a dry heat dryer at 100°C for 24 hours to obtain a dry hollow fiber porous membrane. The resulting hollow fiber porous membrane had a porosity of 75% (dw: 2.5 g, V: 8.0 cm 3 , ρ: 1.24g / cm 3 ), and the PVP content was 2.4% by mass. In addition, when the cross section of the hollow fiber porous membrane was observed by SEM, it was confirmed that there were two regions in which the coarse pores were arranged in parallel and almost continuous layers in the vertical cross section of the hollow fiber porous membrane. The results of analyzing the images obtained by SEM observation are shown in Table 1.
[0072] Using the inner diameter (5.3 mm) of the stainless steel case as a standard, the hollow fiber porous membrane was packed so as to obtain a filling rate as close as possible to 45%, and both ends of the hollow fiber porous membrane were fixed to the ends of the stainless steel case with potting material. Part of the ends of the potting material were cut off to open both sides of the hollow fiber porous membrane, thereby producing membrane module A.
[0073] The water vapor transmission rate and bending resistance of the obtained membrane module A were measured. The results are shown in Table 2. A hollow fiber porous membrane and a membrane module were obtained that not only had excellent water vapor permeability but also had bending durability.
[0074] Example 2 A membrane module B was obtained by the same experimental method as in Example 1, except that a hollow fiber porous membrane having an inner diameter of 886 μm and a membrane thickness of 87 μm was produced using the membrane forming solution and core solution of Example 1. The obtained hollow fiber porous membrane had a porosity of 74% (dw: 2.6 g, V: 8.0 cm 3 , ρ: 1.24g / cm 3 ), and the PVP content was 2.5% by mass. In addition, when the cross section of the hollow fiber porous membrane was observed using an SEM, it was confirmed that there were two regions in which the coarse pores were arranged in parallel and almost continuous layers in the vertical cross section of the hollow fiber porous membrane. The results of analyzing the images obtained by SEM observation are shown in Table 1. The results of analyzing the images obtained by SEM observation are shown in Table 1.
[0075] The water vapor transmission rate and bending resistance of the obtained membrane module B were measured. The results are shown in Table 2. A hollow fiber porous membrane and a membrane module were obtained that not only had excellent water vapor permeability but also had bending durability.
[0076] Example 3 A membrane module C was obtained by the same experimental method as in Example 1, except that a hollow fiber porous membrane with an inner diameter of 702 μm and a thickness of 102 μm was produced using the membrane forming solution and core solution of Example 1. The obtained hollow fiber porous membrane had a porosity of 70% (dw: 2.9 g, V: 7.7 cm 3 , ρ: 1.24g / cm 3 ), and the PVP content was 2.6% by mass. In addition, when the cross section of the hollow fiber porous membrane was observed with an SEM, it was confirmed that there were two regions in which the large pores were arranged in parallel and almost continuous layers in the vertical cross section of the hollow fiber porous membrane. The results of analyzing the images obtained by SEM observation are shown in Table 1.
[0077] The water vapor transmission rate and bending resistance of the obtained membrane module C were measured. The results are shown in Table 2. A hollow fiber porous membrane and a membrane module were obtained that not only had excellent water vapor permeability but also had bending durability.
[0078] Example 4 A membrane module D was obtained by the same experimental method as in Example 1, except that a solution of 20 mass % N,N-dimethylacetamide and 80 mass % water (total mass 100%) was used as the core liquid. The obtained hollow fiber porous membrane had a porosity of 71% (dw: 2.8 g, V: 7.8 cm 3 , ρ: 1.24g / cm 3 ), and the PVP content was 2.4% by mass. In addition, when the cross section of the hollow fiber porous membrane was observed by SEM, it was confirmed that there were two regions in which the coarse pores were arranged in parallel and almost continuous layers in the vertical cross section of the hollow fiber porous membrane. The results of analyzing the images obtained by SEM observation are shown in Table 1.
[0079] The water vapor transmission rate and bending resistance of the obtained membrane module D were measured. The results are shown in Table 2. A hollow fiber porous membrane and a membrane module were obtained that not only had excellent water vapor permeability but also had bending durability.
[0080] Example 5 A membrane module E was obtained in the same manner as in Example 1, except that a hollow fiber porous membrane with an inner diameter of 611 μm and a membrane thickness of 90 μm was produced using a membrane-forming solution prepared by heating and dissolving a total of 100 mass% of 30 mass% polysulfone ("Udel" P-3500 manufactured by Solvay), 2.0 mass% polyvinylpyrrolidone (K30 manufactured by BASF), 67 mass% N,N-dimethylacetamide, and 1 mass% water. The obtained hollow fiber porous membrane had a porosity of 66% (dw: 2.5 g, V: 5.9 cm 3 , ρ: 1.24g / cm 3 ), and the PVP content was 1.2% by mass. In addition, when the cross section of the hollow fiber porous membrane was observed by SEM, it was confirmed that there were two regions in which the coarse pores were arranged in parallel and almost continuous layers in the vertical cross section of the hollow fiber porous membrane. The results of analyzing the images obtained by SEM observation are shown in Table 1.
[0081] The water vapor transmission rate and bending resistance of the obtained membrane module E were measured. The results are shown in Table 2. A hollow fiber porous membrane and a membrane module were obtained that not only had excellent water vapor permeability but also had bending durability.
[0082] Example 6 A membrane module F was obtained in the same manner as in Example 1, except that a hollow fiber porous membrane was produced using a membrane-producing solution prepared by heating and dissolving 18 mass% of polysulfone ("Udel" P-3500 manufactured by Solvay), 7.0 mass% of polyvinylpyrrolidone (K30 manufactured by BASF), 74 mass% of N,N-dimethylacetamide, and 1 mass% of water, totaling 100 mass%. The obtained hollow fiber porous membrane had a porosity of 80% (dw: 2.5 g, V: 10.0 cm 3 , ρ: 1.24g / cm 3 ), and the PVP content was 1.2% by mass. In addition, when the cross section of the hollow fiber porous membrane was observed by SEM, it was confirmed that there were two regions in which the coarse pores were arranged in parallel and almost continuous layers in the vertical cross section of the hollow fiber porous membrane. The results of analyzing the images obtained by SEM observation are shown in Table 1.
[0083] The water vapor transmission rate and bending resistance of the obtained membrane module F were measured. The results are shown in Table 2. A hollow fiber porous membrane and a membrane module were obtained that not only had excellent water vapor permeability but also had bending durability.
[0084] Example 7 A membrane module G was obtained in the same manner as in Example 1, except that a hollow fiber porous membrane was produced using a membrane-producing solution prepared by heating and dissolving 16 mass% of polysulfone ("Udel" P-3500 manufactured by Solvay), 7.0 mass% of polyvinylpyrrolidone (K30 manufactured by BASF), 76 mass% of N,N-dimethylacetamide, and 1 mass% of water, totaling 100 mass%. The obtained hollow fiber porous membrane had a porosity of 84% (dw: 2.4 g, V: 11.6 cm). 3 , ρ: 1.24g / cm 3 ), and the PVP content was 1.2% by mass. In addition, when the cross section of the hollow fiber porous membrane was observed by SEM, it was confirmed that there were two regions in which the coarse pores were arranged in parallel and almost continuous layers in the vertical cross section of the hollow fiber porous membrane. The results of analyzing the images obtained by SEM observation are shown in Table 1.
[0085] The water vapor transmission rate and bending resistance of the obtained membrane module G were measured. The results are shown in Table 2. A hollow fiber porous membrane and a membrane module were obtained that not only had excellent water vapor permeability but also had bending durability.
[0086] Comparative Example 1 A membrane module H was obtained in the same manner as in Example 1, except that a total of 100% by mass of 20% by mass of polysulfone ("Udel" P-3500 manufactured by Solvay), 5% by mass of polyvinylpyrrolidone (K30 manufactured by BASF), 74% by mass of N,N-dimethylacetamide, and 1% by mass of water were dissolved by heating to prepare a membrane forming solution. The obtained hollow fiber porous membrane had a porosity of 70% (dw: 3.0 g, V: 8.0 cm 3 , ρ: 1.24g / cm 3 ), and the PVP content was 3.2% by mass. In addition, when the cross section of the hollow fiber porous membrane was observed with an SEM, it was confirmed that the vertical cross section of the hollow fiber porous membrane had only one central layer in which the coarse pores were arranged in parallel and almost continuous layers. The results of analyzing the images obtained by SEM observation are shown in Table 1.
[0087] The water vapor transmission rate and bending resistance of the obtained membrane module H were measured. The results are shown in Table 2. Since the porous membrane had a high porosity, the water vapor permeability was very excellent, but the bending durability was insufficient.
[0088] Comparative Example 2 28% by mass of polysulfone (Solvay's "Udel" P-3500), 14% by mass of polyvinylpyrrolidone (BASF's K30), 57% by mass of N,N-dimethylacetamide, and 1% by mass of water were heated and dissolved to obtain a membrane-forming stock solution. A solution of 35% by mass of N,N-dimethylacetamide and 65% by mass of water was used as the core liquid. The membrane-forming stock solution was sent to the spinneret section, discharged from the outer tube of the orifice-type double-tube spinneret, and the core liquid was discharged from the inner tube. The discharged membrane-forming stock solution passed through a humidity-controlled dry zone atmosphere, and then led to a coagulation bath and passed through a water washing process at 80°C, and the obtained wet hollow fiber porous membrane was wound into a bundle. The inner diameter of the hollow fiber porous membrane was 644 μm and the membrane thickness was 97 μm. The bundle of wound hollow fiber porous membranes was dried in a dry heat dryer at 100°C for 24 hours to obtain a dry hollow fiber porous membrane. The obtained hollow fiber porous membrane had a porosity of 69% (dw: 2.6 g, V: 6.6 cm 3 , ρ: 1.24g / cm 3 ), and the PVP content was 6.3% by mass. In addition, when the cross section of the porous membrane was observed by SEM, it was confirmed that there was no region in which the large pores were arranged in parallel and almost continuous layers in the vertical cross section of the hollow fiber porous membrane. The results of analyzing the images obtained by SEM observation are shown in Table 1.
[0089] A membrane module I was produced in the same manner as in Example 1, except that the hollow fiber porous membrane obtained in Comparative Example 1 was used, and the water vapor transmission rate was measured and the flex resistance was evaluated. The results are shown in Table 2. The flex resistance was excellent, but the water vapor permeability was low.
[0090] Example 8 After preparing a wound bundle of hollow fiber membranes in the same manner as in Example 7, 170 dtex polyester processed yarn was wound around two hollow fiber membranes in a spiral shape and covered. After that, dry heat drying was performed in the same manner as in Example 7 to obtain a hollow fiber porous membrane unit in a dry state. Using the inner diameter (55 mm) of the stainless steel case as a reference, the obtained hollow fiber porous membrane unit was filled to the closest number to a filling rate of 50%, and both ends of the hollow fiber porous membrane were fixed to the ends of the stainless steel case with a potting material, and a part of the end of the potting material was cut to open both ends of the hollow fiber porous membrane, thereby obtaining a membrane module J. As a result of observing the opening state of the hollow fiber porous membrane from the cut potting cross section, it was confirmed that the hollow fiber membrane was not crushed and was open.
[0091] In addition, when the hollow fiber porous membrane was filled to the closest filling rate of 50% without covering as described above, the opening condition of the hollow fiber porous membrane was observed from a cut cross section of the potting, and it was found that some of the hollow fiber membranes were crushed.
[0092] [Table 1]
[0093] [Table 2] [Explanation of symbols]
[0094] 1: Hollow fiber porous membrane 2: Coarse hole 3: Long diameter of large pores 4: Short diameter of large pores 5: Circumscribed rectangle of the large hole 6: Point of contact between circumscribing rectangle (I) and large hole (I) 7: Point of contact between the circumscribing rectangle (II) and the macropore (II) 10: Region in which large pores are arranged in parallel and in layers almost continuously 20:Air conditioner 21: Air filter 22: Cooling coil 23: Heating coil 24: Membrane module 25: Blower 31: Membrane module 32: Fuel cell 33: Power control unit 34: Motor 35: Battery 40: Air flow meter 41:DRY gas inlet 42: WET gas outlet 43: Membrane module 44:DRY gas outlet 45: Temperature and humidity measurement points 46: WET gas inlet 47: Humidification container 48: Hollow fiber porous membrane 50: Cylinder 51: Hollow fiber porous membrane 60: Regulator 61:DRY gas inlet 62:WET gas 63: WET gas inlet 64: WET gas outlet 65: Pressure gauge 66: Hollow fiber porous membrane 67: Membrane module 68: Solenoid valve 69: Impulse Unit
Claims
1. A hollow fiber porous membrane having a region in which, in a cross section perpendicular to the longitudinal direction of the hollow fiber porous membrane (hereinafter referred to as a "vertical cross section"), coarse pores whose major diameter is 10% or more and 60% or less of the thickness of the hollow fiber porous membrane and 10 μm or more, are layered in parallel and approximately continuous in a direction perpendicular to the thickness direction of the hollow fiber porous membrane, and the hollow fiber porous membrane has a plurality of such regions in the thickness direction of the hollow fiber porous membrane.
2. 2. The hollow fiber porous membrane according to claim 1, wherein the porosity of the entire hollow fiber porous membrane is 60% or more and 85% or less.
3. 3. The hollow fiber porous membrane according to claim 1, wherein the distance between the regions is from 5% to 20% of the thickness of the hollow fiber porous membrane.
4. 3. The hollow fiber porous membrane according to claim 1, wherein the average value of the major axis relative to the minor axis of the coarse pores (a) in the region closest to the inner diameter of the hollow fiber in the vertical cross section and the average value of the major axis relative to the minor axis of the coarse pores (b) are greater than the average value of the major axis relative to the minor axis of the coarse pores (b).
5. 5. The hollow fiber porous membrane according to claim 4, wherein the average ratio of the major axis to the minor axis of the coarse pores (b) is 1.0 or more and 2.0 or less.
6. The hollow fiber porous membrane according to claim 1 or 2, wherein the hollow fiber porous membrane comprises a polysulfone-based polymer and polyvinylpyrrolidone.
7. A hollow fiber porous membrane unit comprising the hollow fiber porous membrane according to claim 6 covered with a covering yarn.
8. A membrane module comprising the hollow fiber porous membrane according to claim 1 or 2, or the hollow fiber porous membrane unit according to claim 7.
9. An air conditioner comprising the membrane module according to claim 8.
10. A fuel cell system comprising at least the membrane module according to claim 8 and a fuel cell.
Citation Information
Patent Citations
Steam-permeable membrane, hollow fiber membrane, and humidifier
JP2011067812A
Water-vapor separation membrane, and method for producing water-vapor separation membrane
JP2020044523A
Cited By
Hollow fiber membrane
JP2026159587A
